Curbing Illegal Grazing Through Mediating Interests of Local Communities in East Nusa Tenggara Province, Indonesia - Kurniadi, Rahman; Maryani, Retno; Wibowo, Lukas Rumboko; Prasetyo, Budiyanto Dwi; Setyowati, Retno (Universitas Negeri Semarang, 2020)
Communities living surrounding forestÃ‚Â haveÃ‚Â used state forest for grazing areaÃ‚Â in East Nusa Tenggara Timur Province, Indonesia for a long time. Ã‚Â However, Indonesia government have not given them a permit for managing state forest. Government willÃ‚Â involve communities in state forest management Ã‚Â Ã‚Â to generate people income but government ,as a principal, was worried that the communities, as agent, Ã‚Â will act in the way contrary to the interest of government. We usedÃ‚Â a principal agent theory to analyze principal agent problems which will occur ifÃ‚Â communities manageÃ‚Â state forest forÃ‚Â silvopasture purpose. The research showed that there are some principal agent problems in silvopasture contract if government give communities a permit for silvopasture purpose, i.e.Ã‚Â communities, as agent, areÃ‚Â not willingÃ‚Â to plant trees and keep forest. Government must control communities to prevent some principal-agent problems in silvopasture contract.